Bioinformatic Analyses of Subgroup-A Members of the Wheat bZIP Transcription Factor Family and Functional Identification of TabZIP174 Involved in Drought Stress Response - Li, Xueyin; Feng, Biane; Zhang, Fengjie; Tang, Yimiao; Zhang, Liping; Ma, Lingjian; Zhao, Changping; Gao, Shiqing (Frontiers in Plant Science, 2016)
Extensive studies in Arabidopsis and rice have demonstrated that Subgroup-A members of the bZIP transcription factor family play important roles in plant responses to multiple abiotic stresses. Although common wheat (Triticum aestivum) is one of the most widely cultivated and consumed food crops in the world, there are limited investigations into Subgroup A of the bZIP family in wheat. In this study, we performed bioinformatic analyses of the 41 Subgroup-A members of the wheat bZIP family. Phylogenetic and conserved motif analyses showed that most of the Subgroup-A bZIP proteins involved in abiotic stress responses of wheat, Arabidopsis and rice clustered in Clade A1 of the phylogenetic tree, and shared a majority of conserved motifs, suggesting the potential importance of Clade-A1 members in abiotic stress responses. Gene structure analysis showed that TabZIP genes with close phylogenetic relationships tended to possess similar exon-intron compositions, and the positions of introns in the hinge regions of the bZIP domains were highly conserved, whereas introns in the leucine zipper regions were at variable positions. Additionally, eleven groups of homologs and two groups of tandem paralogs were also identified in Subgroup A of the wheat bZIP family. Expression profiling analysis indicated that most Subgroup-A TabZIP genes were responsive to abscisic acid and various abiotic stress treatments. TabZIP27, TabZIP74, TabZIP138 and TabZIP174 proteins were localized in the nucleus of wheat protoplasts, whereas TabZIP9-GFP fusion protein was simultaneously present in the nucleus, cytoplasm and cell membrane. Transgenic Arabidopsis overexpressing TabZIP174 displayed increased seed germination rates and primary root lengths under drought treatments. Overexpression of TabZIP174 in transgenic Arabidopsis conferred enhanced drought tolerance, and transgenic plants exhibited lower water loss rates, higher survival rates, higher proline, soluble sugar and leaf chlorophyll contents, as well as more stable osmotic potential under drought conditions. Additionally, overexpression of TabZIP174 increased the expression of stress-responsive genes (RD29A, RD29B, RAB18, DREB2A, COR15A and COR47). The improved drought resistance might be attributed to the increased osmotic adjustment capacity. Our results indicate that TabZIP174 may participate in regulating plant response to drought stress and holds great potential for genetic improvement of abiotic stress tolerance in crops.